Le discours parlementaire sur l’emploi et les droits des femmes en temps de guerre (1939-1945) - Martine Stirling (Revue LISA)
Right from the beginning of the Second World War, the government called upon women: first of all by asking them to house mothers and their children from large cities during the evacuation period; then, by calling upon volunteers for war work and later by enlisting first single women and later married women. Many MPs worried about the impact of such a measure on family and social order. The call to mothers was even more controversial: who was going to look after the children and the home until the men came home?Parliamentary debates of the time show the extent to which the redefinition of the role of women, in a society in crisis, perturbed mentalities and habits, even among women MPs. Although some of them campaigned actively beyond political allegiance in favour of women's work and their improved legal status, others did not hesitate to support measures like the closing down of nurseries even though they could have had a positive long term impact on the future of British women. The animated debates transcribed by Hansard reveal these divisions and open a window on a whole new line of thinking which started during these difficult years on the position and role of women in British society. In this sense, they are an essential primary source on gender issues.